2007
DOI: 10.1007/s10461-007-9235-6
|View full text |Cite
|
Sign up to set email alerts
|

Housing Stability Over Two Years and HIV Risk among Newly Homeless Youth

Abstract: The stability of living situation was examined as a predictor of young people's HIV-related sexual and drug use acts two years after leaving home for the first time. Newly homeless youth aged 12-20 years were recruited in Los Angeles County, California, U.S.A. ( n = 261) and Melbourne, Australia ( n = 165) and followed longitudinally at 3, 6, 12, 18, and 24 months. Their family history of moves and the type and frequency of moves over the two years following becoming newly homeless were examined. Regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…While the methods and findings of these studies vary considerably, there are some consistent themes. The most consistent finding is that drug and alcohol abuse predicted fewer days housed relative to days homeless (Rosenthal et al, 2007;Tevendale et al, 2011;Roy et al, 2014). A greater number of days housed was associated with better connections with peers and family (Slesnick, Bartle-Haring, et al, 2008;Milburn et al, 2009), less risk behavior , being female , past and current engagement in education (Milburn et al, 2009;Roy et al, 2014), being younger and having been homeless for a shorter period of time (Tevendale et al, 2011).…”
Section: Pathways Out Of Homelessnessmentioning
confidence: 94%
See 1 more Smart Citation
“…While the methods and findings of these studies vary considerably, there are some consistent themes. The most consistent finding is that drug and alcohol abuse predicted fewer days housed relative to days homeless (Rosenthal et al, 2007;Tevendale et al, 2011;Roy et al, 2014). A greater number of days housed was associated with better connections with peers and family (Slesnick, Bartle-Haring, et al, 2008;Milburn et al, 2009), less risk behavior , being female , past and current engagement in education (Milburn et al, 2009;Roy et al, 2014), being younger and having been homeless for a shorter period of time (Tevendale et al, 2011).…”
Section: Pathways Out Of Homelessnessmentioning
confidence: 94%
“…Although not focused on transitions away from homelessness specifically, there are some longitudinal quantitative studies of homeless youth that have examined days housed in a given period of time-a variable that is relevant to the process of exiting homelessness (Barber et al, 2005;Slesnick, Kang, Bonomi, & Prestopnik, 2008, Slesnick, Bartle-Haring, Dashora, Kang, & Aukward, 2008Milburn et al, 2009;Rosenthal et al, 2007;Tevendale, Comulada, & Lightfoot, 2011;Roy et al 2004). While the methods and findings of these studies vary considerably, there are some consistent themes.…”
Section: Pathways Out Of Homelessnessmentioning
confidence: 99%
“…In and Rahimian et al's (1992) research on homeless men, and Tomas and Dittmar's (1995) study of homeless women, participants appeared to be less mobile than the participants for this study. However, DeVerteuil's (2003) study of homeless women and Rosenthal et al's (2006) research on homeless youth found higher rates of mobility. Cloke et al's (2001a) work has emphasized the importance of local factors in shaping homeless people's lives, which exacerbates the difficulty in comparing different studies.…”
Section: Reasons For Moving Away From Reservesmentioning
confidence: 99%
“…[1][2][3][4] Housing instability has been operationalized in a variety of ways including being "literally homeless" (i.e., living on the street or outdoors) or living in a temporary housing situation such as a shelter or single-room occupancy (SRO). 5,6 There is a tendency among researchers to focus on the physical place or structure of residence.…”
Section: Introductionmentioning
confidence: 99%